Validation of PROMIS(®) Physical Function Computerized Adaptive Tests for Orthopaedic Foot and Ankle Outcome Research - Hung, Man (Springer US, 2013)
BACKGROUND: In 2012, the American Orthopaedic Foot & Ankle Society(®) established a national network for collecting and sharing data on treatment outcomes and improving patient care. One of the network’s initiatives is to explore the use of computerized adaptive tests (CATs) for patient-level outcome reporting. QUESTIONS/PURPOSES: We determined whether the CAT from the NIH Patient Reported Outcome Measurement Information System(®) (PROMIS(®)) Physical Function (PF) item bank provides efficient, reliable, valid, precise, and adequately covered point estimates of patients’ physical function. METHODS: After informed consent, 288 patients with a mean age of 51 years (range, 18–81 years) undergoing surgery for common foot and ankle problems completed a web-based questionnaire. Efficiency was determined by time for test administration. Reliability was assessed with person and item reliability estimates. Validity evaluation included content validity from expert review and construct validity measured against the PROMIS(®) Pain CAT and patient responses based on tradeoff perceptions. Precision was assessed by standard error of measurement (SEM) across patients’ physical function levels. Instrument coverage was based on a person-item map. RESULTS: Average time of test administration was 47 seconds. Reliability was 0.96 for person and 0.99 for item. Construct validity against the Pain CAT had an r value of −0.657 (p < 0.001). Precision had an SEM of less than 3.3 (equivalent to a Cronbach’s alpha of ≥ 0.90) across a broad range of function. Concerning coverage, the ceiling effect was 0.32% and there was no floor effect. CONCLUSIONS: The PROMIS(®) PF CAT appears to be an excellent method for measuring outcomes for patients with foot and ankle surgery. Further validation of the PROMIS(®) item banks may ultimately provide a valid and reliable tool for measuring patient-reported outcomes after injuries and treatment. LEVEL OF EVIDENCE: Level III, diagnostic study. See Instructions for Authors for a complete description of levels of evidence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-013-3097-1) contains supplementary material, which is available to authorized users.